Does Growth Have an Impact on CO2 Emission in ASEAN Countries? - Pratiwi, Ida Ayu Meisthya; Purbadharmaja, Ida Bagus Putu; Yasa, I Made Putra (Department of Development Economics, Universitas Sriwijaya, 2024)
The impact of global warming is alarming, posing significant threats to human health and the environment. They were primarily caused by increased greenhouse gases (GHG), especially CO2, which accounts for 70% of emissions. This study analyzes the impact of the Human Development Index (HDI), Gross Domestic Product (GDP) per capita, and population on CO2 emissions in ASEAN countries using a panel data regression methodology and secondary data from the World Bank and Global Economy Website (2000-2020). Fixed Effect Model Result via E-views 10 reveals that HDI and population have positive but non-significant effects on CO2 emissions. In contrast, GDP per capita has a positive and significant effect, driven by increased consumption of fossil fuels. Governments play a crucial role in mitigating these effects through renewable energy, clean technologies, and environmental education to ensure sustainable development. Future research needs to design incentives to support environmental and economic sustainability.